2004
DOI: 10.1038/sj.bjc.6601975
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of genomic polymorphisms: prediction of clinical outcome to 5-FU/oxaliplatin combination chemotherapy in refractory colorectal cancer

Abstract: In this marker evaluation study, we tested whether distinct patterns of functional genomic polymorphisms in genes involved in drug metabolic pathways and DNA repair that predict clinical outcome to 5-fluorouracil (5-FU)/oxaliplatin chemotherapy in patients with advanced colorectal cancer could be identified. Functional polymorphisms in DNA-repair genes XPD, ERCC1, XRCC1, XPA, and metabolising genes glutathione S-transferase GSTP1, GSTT1, GSTM1, and thymidylate synthase (TS) were assessed retrospectively in 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
272
10
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(304 citation statements)
references
References 38 publications
19
272
10
3
Order By: Relevance
“…Previous reports have revealed significant associations between XPD or XRCC1 gene polymorphisms and survival of lung or colorectal cancer patients treated with platinum-based chemotherapy or radiotherapy (Park et al, 2001;Gurubhagavatula et al, 2004;Stoehlmacher et al, 2004;Yoon et al, 2005). Concerning bladder cancer, Gu et al (2005) showed that the NER gene Sak et al (2005) indicated that high expression levels of APE1 and XRCC1 are associated with improved cancer-specific survival following radical radiotherapy in muscle-invasive bladder cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports have revealed significant associations between XPD or XRCC1 gene polymorphisms and survival of lung or colorectal cancer patients treated with platinum-based chemotherapy or radiotherapy (Park et al, 2001;Gurubhagavatula et al, 2004;Stoehlmacher et al, 2004;Yoon et al, 2005). Concerning bladder cancer, Gu et al (2005) showed that the NER gene Sak et al (2005) indicated that high expression levels of APE1 and XRCC1 are associated with improved cancer-specific survival following radical radiotherapy in muscle-invasive bladder cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Modulation of repair capacity by the SNPs in DNA repair genes might therefore affect response and prognosis following platinumbased chemoradiotherapy (CRT) for cancer. The associations between SNPs and clinical response or prognosis have been reported in patients with lung or colorectal cancer treated with platinum-based chemotherapy or radiotherapy (Park et al, 2001;Gurubhagavatula et al, 2004;Ryu et al, 2004;Stoehlmacher et al, 2004;Zhou et al, 2004;Yoon et al, 2005).…”
mentioning
confidence: 99%
“…77 Contradictory results were published by others who suggested that ERCC1 polymorphism, T/T, at codon 118, was associated with poorer response to FOLFOX and shorter progression-free survival (PFS). [78][79][80] Other researchers have shown that low levels of ERCC mRNA expression are correlated to better response to oxaliplatin combination therapy and survival. 81,82 In any case, inspite of the contrasting results about the specific codon genotypes, it seems that a change of function and expression of the DNA-repairing enzymes does affect the chemotherapy efficacy.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%
“…88 For example, polymorphism of the GSTP1 gene (allele 105 Ile/Ile) was associated with increasing risk of progression and mortality in patients treated with oxaliplatin-based chemotherapy in contrast to the favorable genotype, GSTP1-105 Val/Val. 80 Overexpression of GSTP1 has been shown in CRC tumors, especially of the mucinous type, and may be responsible for diminished oxaliplatin activity and response. 89 Though there are polymorphisms of GSTT1 and M1 genes reported to be related to clinical response in breast cancer and childhood leukemia, no similar association has been found in colorectal cancer.…”
Section: Genetic Alterations In Crcmentioning
confidence: 99%
“…The presence of polymorphisms in these genes modulates their expression and the possibility of being determined in peripheral blood makes its analysis easier. The analysis of polymorphisms in repair genes, especially ERCC1 and XRCC1 associated or not with TS polymorphisms, especially TS 3' URL, achieves significant results [6][7][8]. In the work by , the united determination of ERCC1 polymorphisms and TS 3' URL allows the separation of two sub-groups of patients treated with FOLFOX or CAPOX obtaining a different response to capecitabine or 5FU combined with oxaliplatin.…”
mentioning
confidence: 99%